The Impact of Nitric Oxide Toxicity on the Evolution of the Glutathione Transferase Superfamily: A PROPOSAL FOR AN EVOLUTIONARY DRIVING FORCE - Bocedi, Alessio (American Society for Biochemistry and Molecular Biology, 2013)
Glutathione transferases (GSTs) are protection enzymes capable of conjugating glutathione (GSH) to toxic compounds. During evolution an important catalytic cysteine residue involved in GSH activation was replaced by serine or, more recently, by tyrosine. The utility of these replacements represents an enigma because they yield no improvements in the affinity toward GSH or in its reactivity. Here we show that these changes better protect the cell from nitric oxide (NO) insults. In fact the dinitrosyl·diglutathionyl·iron complex (DNDGIC), which is formed spontaneously when NO enters the cell, is highly toxic when free in solution but completely harmless when bound to GSTs. By examining 42 different GSTs we discovered that only the more recently evolved Tyr-based GSTs display enough affinity for DNDGIC (K(D) < 10(−9) m) to sequester the complex efficiently. Ser-based GSTs and Cys-based GSTs show affinities 10(2)–10(4) times lower, not sufficient for this purpose. The NO sensitivity of bacteria that express only Cys-based GSTs could be related to the low or null affinity of their GSTs for DNDGIC. GSTs with the highest affinity (Tyr-based GSTs) are also over-represented in the perinuclear region of mammalian cells, possibly for nucleus protection. On the basis of these results we propose that GST evolution in higher organisms could be linked to the defense against NO.